Analisa Mampu Redam Komposit Polyester Berpenguat Limbah Filter Rokok - Prayudhi, Muhammad Mirdhad; Samhuddin, Samhuddin; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Wastes that we often encounter easily is waste from cigarette filters, one example of its utilization is the utilization of wast .filter. filter cigarettes as a composite mixture, by utilizing materials originating from waste which are easy to obtain by utilizing cigarette filter waste as a sound absorbing material. this study aims to determine the composition of the composite mixture reinforced by cigarette filter waste on sound intensity and sound absorption coefficient. The production method is with a fraction of 30%: 70%, 44%: 56%, and 51%: 51%, which is the best composite fraction with respect to sound intensity values and sound absorption coefficient values, composite materials with a frequency of 510 Hz get sound intensity values the highest is the 30%:70% fraction of 104,867 dBa. and the lowest is the 51%:49% fraction, which is 96.676 dBa, and the highest sound absorption coefficient is the 51%:49% fraction of 0.196 and the lowest is the 30%-70% fraction, namely 0.129, so it can be concluded that the smaller the fiber fraction of the acoustic material of cigarette filter waste, the higher the sound absorption coefficient produced. The best sound absorption coefficient value is obtained for the material acoustic with a fraction of 51% :51% frequency of 510 Hz which is 0.196. Keywords: Acoustic, Boko, Composite, Noise, Waste.